Corporate governance in South Africa : the role of institutional investors - Bhikha, Vishal (Department of Finance and Tax, 2015)
Corporate governance has become the slogan of the global investment arena over the past decade. Corporate scandals and collapses with major loss to shareholders have noted a change in investors' attitude towards this topic. Corporate governance has not only become important for the survival of companies in the global economy, a set corporate governance framework too is required to merely attract capital for start-ups. This study focuses on the institutional investors in South Africa, and their attitudes towards current corporate governance standards in South Africa, and attitude to governance reform. The aims of this study: * To accentuate the significance, features and benefits of corporate governance in light of the empirical analysis; * To understand South African institutional investor environment better, and their monitoring and participating roles in corporate governance for investment in listed corporate entities; * Review the key criteria factored into investing, and how these are monitored on an on-going basis. Corporate governance criteria in specific was used; * Highlight the attitudes of South African institutional investors to corporate governance in South Africa, and their perception on corporate governance reform; * Review weakness in findings in light of the empirical study and analytical framework and summarise recommendations given the outlook for this sector. We introduce the topic of corporate governance and the concept of agency theory which highlights the reasons behind opportunistic behaviour which occurs at different levels within corporate organisations. We further discuss the change in attitudes of institutional investors on the back of corporate scandals, as well as the reasons and remedies of institutional activism. A background of South African institutional investors is also conducted, with a review of current legislation and corporate governance reform mechanisms applicable to South Africa. Following this is a broad literature review on the quantitative as well as qualitative information needs of institutional investors; this forms the basis for the structure of our questionnaires conducted. The last section draws on the critical findings and insights (including quotes from the interviews) on the role of institutional investors in South Africa, followed by the summary and limitations of this study.